“Agora é tudo mato” – intervenções na cafeicultura na serra de Baturité: discursos, sujeitos e ressignificações (1967-1990) - Morais, Leonardo Noberto de (2024)
The coffee cultivation in the Serra de Baturité has been a significant agricultural and economic activity since the region's settlement in the 19th century. Around this activity, a tradition emerged with diverse customs, alongside a survival dynamic for men and women who relied on this agricultural culture for their livelihoods. The various stages of production, particularly harvesting, involved a considerable number of people and sparked social mobilizations. However, from the 1960s onward, new approaches to thinking about and producing mountain coffee emerged, primarily through modernizing interventions that reshaped this agricultural culture. These policies were spearheaded by the State, represented by the Brazilian Coffee Institute (IBC), which aimed to rethink and rationalize Brazilian coffee farming between the 1960s and 1970s. They developed new practices for the region's coffee cultivation, driven by a modernizing ideal focused on high productivity and capital-oriented production. Nevertheless, these modernizations in mountain coffee farming failed to meet the State's productivity expectations, leading to setbacks, impacts, adaptations, and new production imperatives for the region's coffee culture and its stakeholders. This period brought profound reinterpretations to their lives, survival strategies, and the coffee culture itself. This study seeks to analyze how interventions in mountain coffee farming silenced the experiences of individuals by developing new productive and structural meanings primarily based on agricultural modernization, without considering the specificities and experiences of the stakeholders. We also aim to understand the work dynamics and customs of the rural men and women involved in coffee farming during these interventions. Lastly, we explore how stakeholders and the Serra de Baturité coffee tradition adapted, resisted, and reinterpreted their dynamics post-interventions, considering the involvement of new discourses and social actors such as environmental and tourism perspectives. The study draws on written sources like planning manuals, technical studies, journalistic articles, and periodicals. Additionally, oral history and life experiences of various men and women, whom we consider the coffee stakeholders, are crucial sources.